Processo de institucionalização da educação à distância: o caso da universidade federal de campina grande - UFCG - Macêdo , Albernes Alcântara de (2017)
This study aims to present the particularities presented in the development of Distance Education (EAD) in Brazil, focusing mainly on the attempt to understand how the process of institutionalization of this modality of teaching is developing and, especially, if it lines up to the institutional proposal of the Federal University of Campina Grande. Thus, the research begins and is outlined with the general objective of understanding the process of institutionalization of Distance Education at the Federal University of Campina Grande - UFCG and its adequacy to the institutional proposal of the University, thus seeking, in its specific objectives, to identify, in the Institutional management of the UFCG, the administrative, financial / budgetary aspects that influence the institutionalization in the AED in this Institution of Higher Education; To analyze, in the didactic-pedagogical structure of the UFCG, the academic aspects that act in that institutionalization in the EAD in this Institution of Higher Education; Present proposals to contribute to the development of the process of institutionalization of Distance Education at the UFCG. In order to achieve these objectives, the study is based theoretically on the historical vision of EAD in the world and in Brazil, structured in the definitions proposed in the EAD literature; Also follows the managerial approaches of the EAD, as well as, it is based on the national legislation that bases and structures EAD in the country. Methodologically, the research has an applied nature, since it will seek to interweave the theoretical reflection about the EAD/UFCG phenomenon, focusing on the institutionalization process of the EAD in the institution and propose a practical application of this study to CFU and brings as a predominant focus the qualitative research through of documentary analysis, carried out through bibliographic research and documentary research, carried out in the institutional and academic documents of the Federal University of Campina Grande - UFCG, in order to identify and, above all, to understand the aspects that influence the process of institutionalization of Distance Education in the Organization. From the analysis and interpretation of the results of this research, some proposals that contribute to the process of institutionalization of the EAD were presented, thus evidencing a practical applicability of this study within the scope of the Federal University of Campina Grande - UFCG. Lastly, in the final considerations about the content of Distance Education researched, it was noticed that the great challenge for the managers of the EAD beyond managing the particularities required by this modality of education is of fundamental importance to conduct the way the EAD will be implemented and especially, as perceived by all involved in the institution.